EVALUATION OF DRINKING WATER QUALITY - KRISHNA VAIDYA; MOHINI GADHIA (International Journal of Pharma and Bio Sciences, 2012)
Navsari district is located in the south eastern part of Gujarat state in the coastal lowland along Purna River in India. Its geographical coordinates are 20°51' 0" North, 72°55' 0" East. In the present study, the physico-chemical parameters of water resources of Navsari district (Gujarat, India) have been analyzed regarding their suitability for drinking purpose. The study was carried out by collection of water samples from six sampling sites. These samples are analyzed for turbidity, pH, total solids, total suspended solids, total dissolved solids, total hardness, magnesium hardness, calcium hardness, phenolphthalein alkalinity, total alkalinity. The analyzed result is compared with permissible limits as prescribed by WHO, GPCB for drinking water quality.